2006
DOI: 10.1124/jpet.106.104463
|View full text |Cite
|
Sign up to set email alerts
|

Functional Selectivity and Classical Concepts of Quantitative Pharmacology

Abstract: The concept of intrinsic efficacy has been enshrined in pharmacology for half of a century, yet recent data have revealed that many ligands can differentially activate signaling pathways mediated via a single G protein-coupled receptor in a manner that challenges the traditional definition of intrinsic efficacy. Some terms for this phenomenon include functional selectivity, agonist-directed trafficking, and biased agonism. At the extreme, functionally selective ligands may be both agonists and antagonists at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
910
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 992 publications
(950 citation statements)
references
References 100 publications
21
910
0
5
Order By: Relevance
“…The reasons why tolerance develops to the effects of some 5-HT 2C receptor agonists but not others are not known. It may be that any variations in tolerance profiles between these 5-HT 2C receptor agonists relate to how these compounds differentially activate distinct intracellular signalling pathways coupled to 5-HT 2C receptors (eg Berg et al, 2001;Stout et al, 2002), a phenomenon termed functional selectivity (Urban et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons why tolerance develops to the effects of some 5-HT 2C receptor agonists but not others are not known. It may be that any variations in tolerance profiles between these 5-HT 2C receptor agonists relate to how these compounds differentially activate distinct intracellular signalling pathways coupled to 5-HT 2C receptors (eg Berg et al, 2001;Stout et al, 2002), a phenomenon termed functional selectivity (Urban et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of selective receptor modulators is probably most widely recognized in the nuclear receptor field where it has had an enormous impact on steroid receptor targeted therapeutics (Jordan, 2007). However, recent studies have demonstrated that the general concept of selective receptor modulators also applies to GPCRs (for recent reviews see (Galandrin et al, 2007;Kenakin, 2004;Neubig, 2007;Perez and Karnik, 2005;Urban et al, 2007;Violin and Lefkowitz, 2007)) and this evolution in our understanding again promises to have important consequences for drug development (Mailman, 2007). New terms have been coined to describe the idea that agonists can selectively activate different signaling pathways and responses via a single GPCR.…”
Section: Ligand Binding and Functional Selectivity In G Protein Couplmentioning
confidence: 99%
“…For many members of this receptor family it is now well established that they oscillate among multiple conformations which can be differentially stabilized by ligands thus permitting access to only a subset of the complete repertoire of receptor behaviors [2][3][4][5][6][7][8] . This phenomenon, also referred to as biased agonism, functional selectivity or signal trafficking, has an important impact on GPCR drug discovery because it raises the possibility to design signaling pathway-specific therapeutics.…”
Section: Introductionmentioning
confidence: 99%